Pendidikan Karakter Religius di Masa Pandemi Covid-19 di Madrasah Ibtidaiyah Nurul Ulum Unggulan Sukorejo Bojonegoro - Firda Zakiyatur Rofi'ah; Zaini Miftah; Dian Puspita Anggraini (LP. Ma'arif Janggan Magetan, 2023)
Education, which should ideally be carried out face-to-face, during the Covid-19 pandemic is the opposite. The pandemic is one of the obstacles in the educational process, as well as the implementation of character education. Madrasah Ibtidaiyah Nurul Ulum Unggulan Sukorejo is one of the madrasas in Bojonegoro which has excellent programs, one of which is character education, namely religious character. The purpose of the study was to describe the application and obstacles and solutions in the application of religious character education during the Covid _19 pandemics at Madrasah Ibtidaiyah Nurul Ulum Unggulan Sukorejo Bojonegoro. This study used the descriptive qualitative method. The research instruments are interviews, observation, and documentation. Then the data sources in this study were the head of the madrasa, waka curriculum, ustad - uztadzah and students. The data analysis of this research used data reduction, data presentation, and verification. Implementation of religious character education at Madrasah Ibtidaiyah Nurul Ulum Superior during the covid-19 pandemic. First, the application of the character of obedience to Allah SWT is carried out through the Duha prayer whose assistance is fully entrusted to the parents. The teacher monitors students through photo evidence of children who are praying Dhuha which are sent on WhatsApp groups. Second, the application of the character of respect for others is carried out in the following ways: a. Say and answer greetings. b. Same-gender handshake. c. To say thanks. d. Speak politely. e. Bending the body when passing the ustadz / ustadz. f. Prioritize ustadz / ustadz when passing. Third, the application of polite character is carried out by getting off the vehicle and walking when entering and leaving the madrasa. This also applies to students who are accompanied by their parents or use their own bicycles. Fourth, the application of the character of discipline is carried out at the time of entering the lesson, that is, arriving earlier than the time of entering the lesson. The obstacles faced in the application of religious character education during the pandemic are many habits that are forgotten by students, time in madrasas is not optimal because learning hours are very limited (limited by government regulations), and escort and direction when at home from parents are less than optimal. because of the background of parents who work a lot. The solutions applied to the obstacles to the implementation of character education during the pandemic are continuous evaluation, extra monitoring from ustad/ustadzah, and the formation of a student discipline team.